Chaos in the Sporting World over Russia's War of Aggression: Political Neutrality in Light of Human Rights Protection - Wiater-Hellgardt, Patricia (Business and Human Rights Journal, 2023)
There is currently disagreement in the international sports world about whether Russian and Belarusian athletes should be admitted to international competitions. While initially proposing to ban these athletes, the International Olympic Committee (IOC) is now recommending that sports federations readmit Russian and Belarusian athletes under certain conditions. The IOC believes that this is unavoidable in order to respect human rights. Sports federations are invoking their autonomy on this issue, with some following the IOC's advice, some maintaining a ban, and others allowing unconditional participation. This piece seeks to correct the IOC's interpretation of the applicable human rights standard. It asserts that sporting bodies must respect human rights, and that the principles of autonomy and neutrality of sport must be considered in light of internationally recognised human rights standards. If these are used as a yardstick, it becomes clear that collective exclusion can be justified in the extreme case of a war of aggression.
CRIS-Team Scopus Importer:2023-09-29
Keywords: discrimination; international sports federations; political neutrality; proportionality; Russia's war of aggression